Elevations in T‐helper‐2‐initiating cytokines (interleukin‐33, interleukin‐25 and thymic stromal lymphopoietin) in lesional skin from chronic spontaneous ('idiopathic') urticaria. (1st May 2015) - Kay, A.B.; Clark, P.; Maurer, M.; Ying, S.
Summary: Background: The mechanism of wealing in chronic spontaneous urticaria (CSU) is largely unknown. We previously demonstrated increased expression of T‐helper 2 [interleukin (IL)‐4 and IL‐5] cytokines in skin biopsies from CSU. This suggested that Th2‐initiating cytokines [IL‐33, IL‐25 and thymic stromal lymphopoietin (TSLP)], released through innate immune mechanisms, may play a role in pathogenesis. Objectives: To identify Th2‐initiating cytokines in lesional and nonlesional skin from patients with CSU and to compare the results with a control group. Methods: Paired biopsies (one from a 4–8 h spontaneous weal and one from uninvolved skin) were taken from eight patients with CSU and nine control subjects, and studied by immunohistochemistry and confocal microscopy. Results: There were increases in IL‐4 + and IL‐5 + cells in lesional skin vs. controls ( P = 0·03 and P < 0·001, respectively) and marked elevations in the numbers of IL‐33 +, IL‐25 + and TSLP + cells in the dermis of lesional skin vs. both nonlesional skin ( P = 0·002, P = 0·01 and P = 0·04, respectively) and controls ( P = 0·001, P < 0·001 and P = 0·005, respectively). There was also a correlation between the numbers of IL‐33 + and IL‐25 + cells ( r = 0·808, P = 0·015). IL‐33 localized to CD31 + endothelial cells, CD90 + fibroblasts, CD68 + macrophages and tryptase + mast cells, whereas IL‐25 was expressed by epithelial cells, mast cells and major basic protein‐positive eosinophils. IL‐33 and IL‐25 were constitutively expressed in the epidermis of both controls and patients with CSU. Conclusions: Increased expression of Th2‐initiating cytokines in lesional skin in CSU suggests that innate pathways might play a role in the mechanism of wealing. As Th2‐initiating cytokines play a role in mast cell activation, inflammation and vascular leakage in CSU, these findings may also have therapeutic implications.